The Tauhid of Imam Al-Asy’ari in The Malay Tradition: An Analysis of Faridat Al-Farāid by Sheikh Wan Ahmad bin Muhammad Zayn - Sisaeng, Affan; AB, Zuherni (Jurnal Pemikiran Islam, 2024)
This article aims to analyze the concept of tauhid (Islamic monotheism) according to Imam Al-Asy’ari as elaborated in the book Faridat al-Farāid fi ilmi al-‘Aqāid by Sheikh Wan Ahmad bin Muhammad Zayn , highlighting its relevance to the Islamic educational tradition in the Malay world. The study employs a descriptive-analytical method using a qualitative approach grounded in library research. The Faridat al-Farāid serves as the primary source, while secondary sources include theological references and scholarly works related to Imam Al-Asy’ari's concept of tauhid. The findings indicate that Imam Al-Asy’ari’s tauhid as presented in the Faridat al-Farāid encompasses three main aspects—dzāt (essence), sifat (attributes), and af’al (acts)—which are explained through 13 obligatory attributes, 13 impossible attributes, and one permissible attribute of Allah SWT. The book adopts a detailed (tafsili) approach to strengthen the understanding of tauhid while bridging textual and rational arguments in line with the Asy’ari school of thought. Furthermore, the book’s relevance lies in its role as a theological guide for traditional Islamic education in the Malay world, integrating textual and rational pedagogies. This study concludes that the Faridat al-Farāid not only reflects Imam Al-Asy’ari’s theological thought but also significantly contributes to Islamic education. Future studies are recommended to explore the application of Asy’ariyah theology in addressing contemporary challenges.